FORMULASI DAN UJI PENERIMAAN KONSUMEN SABUN TRANSPARAN KOMBINASI VCO (VIRGIN COCONUT OIL) DENGAN KATEKIN - Sefrianita Kamal; Lusia Eka Putri; M. Taufik Eka Prasada (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
Soap is a cleancer that every human needs, clean, free of acne and smooth skin is the desire of human every human, especially women. Soap is used as a dirt-cleaning agent, especially for dirt that is a fat or oil by emulsifying them. Stepping from the above statement, in accordance with the concept of bact to nature, then try to develop a formulation of transparent soap, a combination of VCO with catechin. Soap is product of a mixture of salt, sodium with stearic, palmitic and oleic acids containing a few components of myristic acid dan laurate. It is expected later the consumer can accept this formula. Transparent soaps containing catechins are formulated with three consentrates, 0 %, 0.25 %, and 0.5 % each of the formulas evaluated in the from of description, pH, foam power trial, the comparison showed no significant difference of formula 1,2 and 3.